2011
DOI: 10.1253/circj.cj-11-0718
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Isolated Tricuspid Regurgitation Late After Left-Sided Valve Surgery - Clinical Features and Mechanisms -

Abstract: Background: Severe tricuspid regurgitation (TR) sometimes develops late after left-sided valve surgery without left heart failure, pulmonary hypertension or rheumatic tricuspid valve. The purpose of the present study was to investigate clinical characteristics and mechanisms of severe isolated TR late after left-sided valve surgery. Methods and Results:A total of 372 consecutive patients who underwent left-sided valve surgery between 1990 and 2003 and who were followed up with echocardiography for at least 5 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 27 publications
2
27
0
3
Order By: Relevance
“…1,15) However, moderate to severe late functional TR has been reported after isolated MV surgery. 16,17) Because severe late TR is associated with high mortality and morbidity, concomitant TV annuloplasty is recommended for severe TR at the time of MV surgery to prevent progression to functional TR. However, the use of concomitant TV annuloplasty for mild/moderate functional TR remains a controversial subject, 7,8) because limited available data related to the long-term outcomes of concomitant TV annuloplasty exist.…”
Section: Discussionmentioning
confidence: 99%
“…1,15) However, moderate to severe late functional TR has been reported after isolated MV surgery. 16,17) Because severe late TR is associated with high mortality and morbidity, concomitant TV annuloplasty is recommended for severe TR at the time of MV surgery to prevent progression to functional TR. However, the use of concomitant TV annuloplasty for mild/moderate functional TR remains a controversial subject, 7,8) because limited available data related to the long-term outcomes of concomitant TV annuloplasty exist.…”
Section: Discussionmentioning
confidence: 99%
“…1, 13 However, moderate-to-severe late functional TR has been reported after isolated mitral surgery. 14, 15 Because severe late TR is associated with high mortality and morbidity, concomitant TV annuloplasty is recommended at the time of mitral surgery in these patients, to prevent progression of functional TR. However, previous studies have identified various mechanisms of MR, ranging from rheumatic to ischemic disease and other cardiomyopathic processes.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have identified various mechanisms of MR, ranging from rheumatic to ischemic disease and other cardiomyopathic processes. 1,13- 15 The type of MR affects the progression of TR. We therefore focused on degenerative mitral valve leaflet prolapse, which is the most frequent MR condition in the West.…”
Section: Discussionmentioning
confidence: 99%
“…The development of moderate or greater than moderate STR after left-sided valve surgery worsens the long-term prognosis [2,4]. In previous studies, female [5][6][7], mitral stenosis [1], rheumatic etiology [1,6], atrial fibrillation [1,4,6,7], low left ventricular (LV) function [7], dilatation of the left atrium [1,4,5], pulmonary hypertension [5,7], dilatation of the right ventricle [8], preoperative TR severity [4], tricuspid valve (TV) annular dilatation [9], and TV tethering [10] were reported as predictors of STR; however, most of these reports were of patients with mitral valve disease. Although STR complicated with aortic stenosis (AS) is not uncommon [4], there is a lack of information on late STR that has developed after aortic valve replacement (AVR) for AS.…”
Section: Introductionmentioning
confidence: 99%